STUDY OF ASPECTS OF MILK WHEY CONDITIONING BY MICROFILTRATION WITH USING CERAMIC MEMBRANES - Ivan Alekseevich Evdokimov; Evgeniy Romanovich Smirnov; Mariya Ivanovna Shramko; Elena Aleksandrovna Gostischeva (Вестник Северо-Кавказского федерального университета, 2022)
In the article presented materials on milk whey microfiltration with ceramic membranes. Microbiologi- cal and technological parameters were studied on each stage of the process with various temperatures. Tech- nological regimes of acid whey processing are suggested.